Labor and Product Market Reforms and External Imbalances : Evidence from Advanced Economies - Duval, Romain (IMF Working Papers; Working Paper ;, 2021)
We explore the impact of major labor and product market reforms on current account dynamics using a new 'narrative' database of major changes in employment protection for regular workers and product market regulation for non-manufacturing industries covering 26 advanced economies over the past four decades. Our main finding is that product market deregulation is associated with a weakening of the current account, while labor market deregulation is associated with an improvement. These effects are transitory and driven by both saving and investment responses. Labor and product market reforms both have a more positive impact on the current account balance when implemented under weak macroeconomic conditions. Our results are broadly consistent with predictions from recent DSGE models with endogenous producer entry and labor market frictions.